2008
DOI: 10.1158/0008-5472.can-07-5955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on the ATR/Chk1 Pathway in the Epidermis of UVB-Irradiated Mice

Abstract: Administration of caffeine was shown in earlier studies to enhance UVB-induced apoptosis and inhibit UVB-induced carcinogenesis in hairless SKH-1 mice. Here, we describe a potential mechanism for these in vivo effects. A single irradiation of mouse skin with UVB activated the ataxiatelangiectasia mutated-and Rad3-related (ATR) pathway, causing a severalfold increase in keratinocytes with phosphoChk1 (Ser 345 ) and a marked decrease in mitotic keratinocytes with cyclin B1 compared with baseline. When given in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 32 publications
5
56
0
Order By: Relevance
“…Recently, it was shown that both siRNA-triggered inhibition of CHK1 expression as well as caffeine-mediated inhibition of CHK1 activation abrogated checkpoint control and augmented UVB-induced apoptosis in human primary KC. 52 Accordingly, pre-exposure of SKH-1 hairless mice to caffeine resulted in an enhanced rate of UVB-induced apoptosis in the epidermis 53 and protected the animals against photocarcinogenesis. 54 In addition, epidemiological data imply that daily caffeinated coffee consumption decreases the incidence and prevalence of NMSC in Caucasians, 55,56 indicating that CHK1 inhibition is indeed effective in terms of cancer chemoprevention in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that both siRNA-triggered inhibition of CHK1 expression as well as caffeine-mediated inhibition of CHK1 activation abrogated checkpoint control and augmented UVB-induced apoptosis in human primary KC. 52 Accordingly, pre-exposure of SKH-1 hairless mice to caffeine resulted in an enhanced rate of UVB-induced apoptosis in the epidermis 53 and protected the animals against photocarcinogenesis. 54 In addition, epidemiological data imply that daily caffeinated coffee consumption decreases the incidence and prevalence of NMSC in Caucasians, 55,56 indicating that CHK1 inhibition is indeed effective in terms of cancer chemoprevention in humans.…”
Section: Discussionmentioning
confidence: 99%
“…ATR has higher affinity for DNA in UV-damaged cells than in undamaged cells, and damaged DNA stimulates the kinase activity of ATR significantly more than undamaged DNA (34). Caffeine either directly disrupts the ATR/Chk1 checkpoint pathway (35) or inhibits UV-induced phosphorylation of Chk1 and prematurely increases the number of mitotic cells with cyclin B1 that are likely to go on to apoptosis (5). In human keratinocytes, inhibition of the ATR-Chk1 pathway with caffeine augmented UV-induced apoptosis in a p53-independent manner, whereas other known and plausible targets of caffeine were not found to be involved in the UV response (9).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have consistently shown that oral or topical administration of caffeine inhibits SCC development in mice treated with UV light (4)(5)(6)(7)(8). Oral administration of tea inhibited UV-induced carcinogenesis in mice, whereas decaffeinated tea elicited substantially less inhibitory activity, which was restored by caffeine (6).…”
Section: Introductionmentioning
confidence: 99%
“…2). Similar to wildtype MEFs, KCs are highly sensitive to caffeine treatment after UV irradiation (46,47). Thus, KCs lacking PKC␦, such as in squamous papillomas and carcinomas, are also likely to have this dual defect in the response to DNA damage, resulting in both reduced cell cycle arrest and reduced apoptosis (23,24,48).…”
Section: Discussionmentioning
confidence: 99%